Ginsenoside Rk1 alleviates lipopolysaccharide (LPS)-induced cognitive impairment by modulating synaptic plasticity - Zhang, Xuesong; Ning, Funan; Zhang, Biqun; Ji, Jiaqi; Zheng, Junzuo; Hu, Xiaosong; Liu, Zhiang; Ding, Li; Wang, Ping; Lan, Zhou (Frontiers in Pharmacology, 2026)
BackgroundThis study aimed to comprehensively investigate the therapeutic effects of ginsenoside Rk1 on LPS-induced cognitive impairment and elucidate its underlying mechanisms, with a particular focus on synaptic plasticity and related signaling pathways, thereby providing robust theoretical and experimental support for its neuroprotective application.Research MethodsNetwork pharmacology identified potential therapeutic targets and pathways of ginsenoside Rk1 relevant to inflammation-induced cognitive impairment, and molecular docking assessed its binding affinity with key predicted proteins. In vitro, mouse bone marrow-derived macrophages (BMDMs) were used to determine the optimal non-cytotoxic concentration of ginsenoside Rk1 via CCK-8 assay. LPS and ATP were used to induce inflammation, and ELISA and RT-qPCR quantified pro-inflammatory cytokines and mRNA expression of Akt isoforms. For in vivo validation, male C57BL/6 mice were administered ginsenoside Rk1 (at an optimal dose of 20 mg/kg·d−1, i.g.) for 21 days, with LPS (500 μg/kg·d−1, i.p.) challenging on Day 22 and continued treatment for 7 days post-LPS. Cognitive function was assessed using the Morris water maze (MWM). Hippocampal samples were then analyzed for inflammatory factors, synaptic protein expression (PSD-95, SYN by RT-qPCR and immunofluorescence), microglial activation (Iba1 immunofluorescence), and dendritic spine density (Golgi staining).ResultsNetwork pharmacology successfully identified significant overlaps between ginsenoside Rk1 targets and pathways associated with inflammation and cognitive impairment, prominently featuring the PI3K/Akt pathway. Molecular docking simulations confirmed strong binding affinities between ginsenoside Rk1 and key proteins in this pathway. In vitro, ginsenoside Rk1 significantly reduced LPS/ATP-induced levels of TNF-α, IL-1β, and IL-6, and attenuated the upregulation of Akt1, Akt2, and Akt3 mRNA expression. In vivo, ginsenoside Rk1 treatment profoundly improved spatial learning and memory in LPS-challenged mice. This cognitive improvement was paralleled by a significant attenuation of hippocampal neuroinflammation. Crucially, ginsenoside Rk1 significantly reversed LPS-induced synaptic dysfunction, characterized by increased mRNA and protein expression of PSD-95 and SYN, and a marked elevation in neuronal dendritic spine density in the hippocampus.ConclusionThis study provides compelling evidence that ginsenoside Rk1 effectively alleviates LPS-induced cognitive dysfunction by ameliorating neuroinflammation and significantly enhancing synaptic plasticity. The mechanistic insights suggest that these neuroprotective effects are mediated, at least in part, through the modulation of the PI3K/Akt signaling pathway.